IMPLEMENTATION OF EDUCATION MANAGEMENT IN THE ERA OF SOCIETY 5.0 - Arman Paramansyah; Usep Dedi Rostandi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
In the era of society 5.0, people are treated to technology that allows accessing virtual space that feels like physical space in the form of AI (Artificial Intelligence) technology based on big data and robots that support and facilitate human work. If in the industrial revolution 4.0 it was more of an emphasis on business, but in the era of society 5.0, values were born that eliminate social inequality and provide more services and products for the various needs of many people. Educational management has problems covering all problems that are related or related to professional educators, students, curriculum, facilities and infrastructure, and the learning process.